COMPARATIVE INVENTORY CONTROL ANALYSIS WITH ECONOMIC ORDER QUANTITY (EOQ) AND JUST IN TIME METHOD TO MINIMIZE INVENTORY COSTS AT UD. MELATI JAYA - Khairunnisa Almadany; Imamati Zikra Ar Rusyfa; Rizaldy Khair (Journal of Islamic, Social, Economics and Development, 2020)
The research discusses how To Compare Inventory Control Analysis With Economic Order Quantity (EOQ) Method and Just In Time (JIT) Method To Minimize Inventory Costs At UD. Melati Jaya. This study discusses a comparative analysis of the Economic Order Quantity method and the Just In Time method to minimize inventory costs at UD. Jasmine jaya. The data analysis method used is descriptive qualitative method with comparative research that compares the Econimic Order Quantity (EOQ) method with the Just In Time (JIT) method to the cost efficiency at UD. Melati Jaya. The analysis results from the comparative calculation of inventory control show that the Just In Time Inventory Control method is more appropriate to be applied to Ud. Melati Jaya because the total cost of the inventory is smaller than the total cost of the inventory when using the Economic Order Quantity (EOQ) method.